2001
DOI: 10.1063/1.1348318
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin probe force microscopy on InAs thin films grown on GaAs giant step structures formed on (110) GaAs vicinal substrates

Abstract: Surface potential measurements on InAs thin films grown on GaAs giant steps were performed by Kelvin probe force microscopy. We found that the removal of the water-related layer from both surfaces on a sample and a tip was very effective to improve the reliability of the surface potential measurements. The measured potential distribution corresponds to the surface corrugation of the InAs thin films. In addition, the InAs layer thickness dependence of the surface InAs Fermi levels is investigated, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 10 publications
4
15
0
Order By: Relevance
“…It is known that surface potential varies according to the dipole moment of molecules adsorbed on a surface. In the case of a water-related layer on a sample surface, the surface potential of AlGaN/GaN heterostructure and n-GaN is thought to be shielded by the adsorbed water-related layer, which can be easily polarized [21]. Since the surface adsorbed water-related layer could be removed after the thermal treatment, the quantitative and highresolution potential images would be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that surface potential varies according to the dipole moment of molecules adsorbed on a surface. In the case of a water-related layer on a sample surface, the surface potential of AlGaN/GaN heterostructure and n-GaN is thought to be shielded by the adsorbed water-related layer, which can be easily polarized [21]. Since the surface adsorbed water-related layer could be removed after the thermal treatment, the quantitative and highresolution potential images would be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…at the surface the conduction band is below the Fermi level), and an electron accumulation region forms. 33 Accordingly, we varied the pinning potential in the range −0.5 ≤ V pin /E Γ ≤ 0.5 for In 1−x Ga x As, and found a small change in the simulated E THz . In Fig.…”
Section: Surface Space-charge Layermentioning
confidence: 92%
“…Also, the removal of the water-related layer from both surfaces of the sample and the AFM tip was reported to be very important to improve the reliability of the KPFM measurements [47]. Moreover, it was reported that larger humidity levels and a thicker adsorbed water film over the sample surface result in a larger adhesive force between the AFM tip and the sample [36].…”
Section: Fdc-based Characterizationmentioning
confidence: 99%